Sensory Marketing Analysis: Exploring Uncertainty and Contradiction in Consumer Decision-Making. A Multineutrosophic Analysis with ARAS - Eluard Alexander Mendoza Zenozain; Rosa María Criollo Delgado; Julio César Vidal Rischmoller (Neutrosophic Sets and Systems)
Sensory marketing studies how visual, auditory, tactile, olfactory, and gustatory stimuli influence consumer decisions, a complex process characterized by contradictions and uncertainties. Previous research has mainly explored individual senses, leaving a gap regarding the multisensory interactions and their inherent ambiguity. This study addresses this issue by proposing a novel methodological approach combining Multineutrosophic Analysis with the Additive Ratio Assessment (ARAS) method. The proposed framework captures the subjective complexity of sensory experiences, quantifying contradictions and uncertainties typically overlooked by traditional models. Findings indicate that visual stimuli initially dominate consumer attraction but lose strength when conflicting sensations, such as unpleasant smells or inappropriate music, appear. The multineutrosophic ARAS approach identifies nonlinear patterns and accommodates consumer perceptions within a spectrum of truth, indeterminacy, and falsehood. Theoretically, this research integrates neutrosophy into sensory marketing, offering practical guidelines to design balanced multisensory experiences and minimize contradictions. The results highlight personalization and contradiction mitigation as strategic priorities, emphasizing their potential to enhance consumer engagement in competitive markets.